Vilken effekt har lärkrutor på ogräsfloran vid ekologisk höstveteodling? - Gustafsson, Linda (SLU/Dept. of Crop Production Ecology, 2008)
This study forms part of the R&D project "Improved survival of bird chicks in organic fields" managed by the Rural Economy & Agricultural society in Uppsala. The skylark (Alauda arvensis) is a species that has decreased drastically in Sweden as a consequence of more intensive cropping.